THE LEVEL OF KNOWLEDGE REGARDING RECURRENT ASTHMA EXACERBATIONS IN PATIENTS WITH BRONCHIAL ASTHMA - Suwaryo, Putra Agina Widyaswara; Yuwono, Podo; Yuniar, Isma; Waladani, Barkah; Setianingsih, Endah; Bachri, Syamsul (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
Bronchial asthma is a chronic disease that significantly impacts individuals' quality of life. Adequate knowledge about preventing asthma exacerbations is crucial in managing this condition. This research aims to evaluate the level of knowledge regarding bronchial asthma exacerbations among patients seeking treatment at PKU Muhammadiyah Gombong Hospital. The research method employed is observational with a cross-sectional approach. Data were collected through surveys using questionnaires distributed to bronchial asthma patients during the months of March to June 2023. Data analysis was conducted using descriptive methods. The research findings indicate that the majority of bronchial asthma patients at the hospital have insufficient knowledge about asthma exacerbations. Most patients are aged 41-50 years, come from farming backgrounds, and have been suffering from asthma for 5 to 10 years. Despite the majority having higher education, there remains a significant knowledge gap. There is a need for increased education and awareness about bronchial asthma exacerbations among patients, especially those with lower educational backgrounds and from rural areas. These efforts are expected to improve the management and prevention of asthma exacerbations and enhance the overall quality of life for patients